Inhibitory effect of melatonin on cerebral endothelial cells dysfunction induced by methamphetamine via NADPH oxidase-2 - Jumnongprakhon P. (2017)
© 2016 Elsevier B.V. Melatonin is a hormone that mostly produced from the pineal gland, and it performs as a strong neuroprotectant to both neuron and glial cells against methamphetamine (METH)-induced neurotoxicity. Recently, it has been found that METH also damages the blood brain barrier (BBB) structure and function. However, the protective mechanism of melatonin on the BBB impairment caused by METH has not been investigated. In this study, the primary rat brain microvascular endothelium cells (BMVECs) isolated from neonatal rats was used to investigate the protective effect of melatonin on METH-induced BBB impairment and the underlying mechanism. The results demonstrated that melatonin decreased the level of reac tive oxygen species (ROS), reactive nitrogen species (RNS), and apoptosis induced by METH via NADPH oxidase (NOX)-2 since apocynin, a NOX-2 inhibitor abolished those changes. In addition, melatonin was found to improve cell integrity by increasing the transendothelial electric resistance (TEER) values, and up-regulate the tight junction proteins ZO-1, occludin, and claudin-5, thereby decreasing the paracellular permeability caused by METH mediated by NOX-2. Our data suggest that METH induces BBB impairment by mediating NOX-2 activity, and then induces oxidative and nitrative stress, as well as apoptosis, which causes the impairment of cell integrity, and that melatonin reduces these negative effects of METH by mediating via MT1/2 receptors.